Moral judgments influence emotional responses and comment lengths through the moderating role of linguistic style matching - Jinrui Tian; Ronghua Zhang (Scientific Reports)
Abstract The study aims to explore how moral judgment influences negative emotional responses and comment length in reactions to “New Yellow Journalism” on Weibo, as well as how Linguistic Style Matching (LSM) moderates these relationships. The study extracted over 8,000 comments from a recent incident involving fabricated viral news and conducted analytical methods to test our hypotheses. The results demonstrate that negative emotional responses mediate the relationship between moral judgment and comment length. Additionally, LSM moderates both the direct effect of moral judgment on comment length and the indirect effect through negative emotional responses. These findings highlight the psychological mechanisms underlying online public opinion dynamics and offer insights for managing online interactions in the digital media era.